Rancang Bangun dan Pelatihan Penggunaan Sistem Administrasi Taman Pendidikan Al-Quran Al Mursyidien Surabaya - Rani Rotul Muhima; Andy Rachman; Rahmi Rizkiana Putri; Farida Farida; Danang Haryo Sulaksono (LPPM ITATS, 2019)
The administration of TPA Al-Mursyidien was still manual. TPA, which is located on Jalan Semolowaru No. 114-118, Semolowaru Surabaya, has had a number of students to hundreds of santri. This is troublesome for the teacher who is also the TPA administration. TPA already has information and communication technology infrastructure facilities but is still not optimally utilized. In fact, ICT can be used to assist TPA’s administration management. Based on these problems, at the ITATS Informatics Engineering Program (PPM) was made application called the